2022
DOI: 10.1080/19420889.2022.2082736
|View full text |Cite
|
Sign up to set email alerts
|

Tool and techniques study to plant microbiome current understanding and future needs: an overview

Abstract: Microorganisms are present in the universe and they play role in beneficial and harmful to human life, society, and environments. Plant microbiome is a broad term in which microbes are present in the rhizo, phyllo, or endophytic region and play several beneficial and harmful roles with the plant. To know of these microorganisms, it is essential to be able to isolate purification and identify them quickly under laboratory conditions. So, to improve the microbial study, several tools and techniques such as micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 194 publications
0
16
0
1
Order By: Relevance
“…This SynComs approach was used by Lebeis, et al [ 53 ], who revealed that the defense phytohormone salicylic acid modulates bacterial colonization of the roots of Arabidopsis. These available tools allow us to unknot the entangled networks of interactions of fundamental microbiomes or holobionts for efficiently using the root microbiome to intensify crops’ nutrient procurement and fight against biotic and abiotic stress [ 54 ].…”
Section: Communication Between the Root Microbiome And Plant Rootmentioning
confidence: 99%
“…This SynComs approach was used by Lebeis, et al [ 53 ], who revealed that the defense phytohormone salicylic acid modulates bacterial colonization of the roots of Arabidopsis. These available tools allow us to unknot the entangled networks of interactions of fundamental microbiomes or holobionts for efficiently using the root microbiome to intensify crops’ nutrient procurement and fight against biotic and abiotic stress [ 54 ].…”
Section: Communication Between the Root Microbiome And Plant Rootmentioning
confidence: 99%
“…Several authors have described the importance and ecological interpretations of the cross-kingdom co-occurrence networks in the plant microbiome [ 162 , 163 ]. Network analyses have identified the existence of interactions among the myriad of endophytes present in natural communities and other potential higher-order interactions [ 164 ]. Thus, this analysis has contributed to the discovery of hub or keystone microbial taxa in the plant microbiome.…”
Section: Future Perspectives For Xylem Microbiome Analysismentioning
confidence: 99%
“…The plant-associated metagenomes are defined as the set of genes encoded by any particular microbiota that can provide the host plant with critical nutrients, protection from plant pathogens, production of functional plant hormones and tolerance to abiotic stresses, etc. Metagenomics will also contribute to improving our understanding of species composition, genetic diversity, inter-species interactions and species evolution in the context of different ecological niches [ 164 ]. However, to the best of our knowledge, to date, only one study has analyzed the olive xylem microbiome by metagenomic analysis, and was conducted by Giampetruzzi et al (2020) [ 102 ].…”
Section: Future Perspectives For Xylem Microbiome Analysismentioning
confidence: 99%
“…The endo-rhizosphere is inhabited by root endophytes (microbes living inside the roots) while the exophytes (microbes living outside of the roots) inhabit the ecto-rhizosphere [3]. Epiphytic (surface-dwelling) microbes colonize the rhizoplane (Figure 1) [4]. Rhizosphere is home to many organisms including bacteria, fungi, actinomycetes, protozoa, algae, nematodes, and arthropods [1,5].…”
Section: Introductionmentioning
confidence: 99%